Analysis and Maintenance Scheme Research on Disassembly Inspection of Mine-used Flameproof Motors and Electromagnetic Starters - Wu, Zhifeng (International Core Journal of Engineering, 2025)
Mine-used flameproof three-phase asynchronous motors and flameproof intrinsically safe vacuum electromagnetic starters are core electrical equipment in underground coal mine production systems, and their operational reliability directly affects coal mine production efficiency and operational safety. For 7 mine-used motors (internal numbers 5-8014 5-8019) and 2 electromagnetic starters (internal numbers 5-8020 5-8021) entrusted for maintenance by Xi’an Research Institute of China Coal Technology and Engineering Group, this study systematically analyzed the equipment fault types and causes, designed targeted maintenance schemes, and implemented verification based on standards such as Explosive Atmospheres (GB/T 3836 series) and General Technical Conditions for Electrical Equipment Used in Underground Coal Mines (MT/T 551-1996), combined with equipment disassembly inspection data. The results show that the main faults of the motors are concentrated in shell structure damage (screw hole wear, rust), transmission component failure (bearing wear, end cover dimension out-of-tolerance), and winding performance degradation (moisture, burnout); the faults of electromagnetic starters are mainly mechanical component jamming (inflexible handle), electrical accessory aging (cable entry device), and flameproof surface defects (rust). Through the closed-loop maintenance process of "disassembly inspection - repair/replacement - testing", the insulation performance, flameproof performance, and operating parameters of all equipment after maintenance meet national standards, with a 100% qualification rate in the overall machine test. This research provides a technical reference and practical paradigm for the standardized maintenance of high-voltage grade electrical equipment in mines.